An empirical study of the effectiveness of online counseling services from various job settings and features - Sutoyo, Anwar; Supriyanto, Agus; Hendiani, Nurlita (Universitas Islam Negeri Raden Intan Lampung, 2023)
The challenge for future counselors is using technology in counseling. Online counseling is a strategy that can be applied amid the counselee’s doubts about the effectiveness of existing counseling services. This study aims to identify the point of online counseling services from various counseling service settings. The qualitative systematic literature review design is sourced from 9 scientific journals through the semantic scholar database and has been reputable from 2013-2022. The PRISMA flow diagram model is presented—data analysis of 9 articles (out of 588 invalids) through descriptive narrative. The data findings show that it is more effective than face-to-face. School, college, addiction, health, and community counselors can apply for it. Telephone, chat, video, and text features can support multiple counseling approaches. Counselors need to develop the skills and competencies of counselors with online counseling through training and webinars.